Barriers to home‐based palliative care in people with cancer: A qualitative study of the perspective of caregivers. Issue 4 (22nd April 2020) - Hassankhani, Hadi; Rahmani, Azad; Best, Amy; Taleghani, Fariba; Sanaat, Zohreh; Dehghannezhad, Javad
Abstract: Aim: To investigate the barriers to home‐based palliative care for cancer patients from professional caregivers' experiences. Design: A qualitative study. Method: This is a descriptive‐qualitative study carried out in the community‐based care. Twenty‐three participants took part in this study. Data were collected through semi‐structured interviews. Results: Data analysis led to the identification of three category of barriers including the lack of instructions (the lack of clinical practice guidelines, the ambiguity of tariffs and the lack of insurance coverage), family desperation (family views of prognosis, distrust and poverty) and lack of professionalism (limited knowledge, the use of amateur nurses and siloed care). Developing a care protocol and providing resources support contribute to the development of home‐based palliative care. Moreover, the education of families and training courses for nurses must be fostered.